After the Crisis A “New Normal” for Democratic Citizenship? - Blumler, Jay G.; Coleman, Stephen (Javnost-The Public, 2021)
The global pandemic and consequent economic tumult have strained conventional theoretical accounts of what it means to be a citizen. The notion of a “new normal” has been widely adopted to describe the potential historical reframing that the pandemic has engendered. Drawing on previous theoretical accounts of crises and their ramifications, this article explores how the communicative features of democratic citizenship might be imagined and practised differently in the aftermath of the pandemic. It considers the spatial and ontological recasting of the idea of the civic public that has been precipitated by the present global crisis. The article calls for the elaboration of a language of public discourse by which people can develop new forms of communicative agency, enabling them to respond to urgent contingencies; negotiate tensions between historical possibilities; and cultivate emergent futures.